2022
DOI: 10.4269/ajtmh.21-0532
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Characteristics of Lactate Dehydrogenase on a Multiplex Assay for Malaria Detection Including the Zoonotic Parasite Plasmodium knowlesi

Abstract: Plasmodium lactate dehydrogenase (pLDH) is a common target in malaria rapid diagnostic tests (RDTs). These commercial antibody capture assays target either Plasmodium falciparum–specific pLDH (PfLDH), P. vivax–specific pLDH (PvLDH), or a conserved epitope in all human malaria pLDH (PanLDH). However, there are no assays specifically targeting P. ovale, P. malariae or zoonotic parasites such as P. knowlesi and P. cynomolgi. A malaria multiplex array, carrying the specific antibody spots for PfLDH, PvLDH, and Pan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 51 publications
4
12
0
Order By: Relevance
“…Importantly, we found that the assay requires further development for precise identification of non-falciparum species. The high level conservation of the LDH protein among the different Plasmodium species, with resultant cross-reacting antibody specificity, means that the Pf-LDH cannot distinguish P. falciparum from P. malariae 7 and P. ovale , and is consistent with previous findings 10 . Despite this, it was possible to differentiate P. malariae and P. ovale from P. falciparum by using the lack of HRP2 positivity.…”
Section: Discussionsupporting
confidence: 88%
See 4 more Smart Citations
“…Importantly, we found that the assay requires further development for precise identification of non-falciparum species. The high level conservation of the LDH protein among the different Plasmodium species, with resultant cross-reacting antibody specificity, means that the Pf-LDH cannot distinguish P. falciparum from P. malariae 7 and P. ovale , and is consistent with previous findings 10 . Despite this, it was possible to differentiate P. malariae and P. ovale from P. falciparum by using the lack of HRP2 positivity.…”
Section: Discussionsupporting
confidence: 88%
“…In addition to demonstrating known P. knowlesi cross-reactivity with Pf-LDH 17 , 19 , the platform’s diagnostic performance for P. knowlesi revealed strong cross reactivity with the P. vivax marker (Pv-LDH) as previously reported with both cultured A1H1 strain samples 10 and using other diagnostic methods 18 , 34 , 35 . The superior sensitivity of RDTs targeting Pv-LDH in detecting P. knowlesi over P. vivax has previously been reported 35 and was seen in our plasma samples.…”
Section: Discussionsupporting
confidence: 65%
See 3 more Smart Citations